2013
DOI: 10.1155/2013/842673
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ocular Manifestations and Their Complications as Opposed to Visual Acuity and Treatment in Behcet's Disease

Abstract: The aim of this study was to analyze ocular manifestations, their complications, and treatment in a sample of 40 patients with confirmed Behcet's disease. Results. Serofibrinous iridocyclitis was the most common form of uveitis (60%). Retinal periphlebitis manifested in 92.5% of cases, and periphlebitis in conjunction with periarteritis was diagnosed in 72.5% of cases. Macular edema was the most frequent complication on the posterior segment (60%) and it correlated with periphlebitis (P = 0.45) and periphlebit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is noteworthy that the literature encloses some controversial studies regarding the correlation between macular thickness and visual acuity. Several studies reported moderate to strong correlations between macular thickness and visual acuity, however, some reported weak or no correlation 9 , 10 , 11 , 12 , given the fact that the alterations or disruption of particular retinal sublayers, including ORL, may be associated with visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the literature encloses some controversial studies regarding the correlation between macular thickness and visual acuity. Several studies reported moderate to strong correlations between macular thickness and visual acuity, however, some reported weak or no correlation 9 , 10 , 11 , 12 , given the fact that the alterations or disruption of particular retinal sublayers, including ORL, may be associated with visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 7 8 ] Previous studies have reported many systemic treatments with limited success in improving VA (8.8–24.8%) in BD with ocular involvement. [ 9 10 11 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Classically it presents with a triad of oral aphthous ulcers, genital ulcers, and uveitis. Nevertheless, it can also compromise other systems and organs less frequently, such as the central nervous system, cardiovascular, skin, gastrointestinal, renal, pulmonary, and musculoskeletal systems [1][2][3][4].…”
mentioning
confidence: 99%
“…The prevalence of BD varies with demographic profiles and is determined by environmental and genetic factors [2]. Turkey has the highest prevalence of BD, with 420 per 10,000 inhabitants [1,5].…”
mentioning
confidence: 99%